The Influence of Organizational Culture, Quality of Human Resources, Motivation, and Work Discipline on Employee Performance - Susanti, Ervin Nora; Nasrul, Herni Widiyah; Octaria, Metha; Hakim, Lukmanul; Ismanto, Widodo; Desfika, Indri (International Conference on Business Management and Accounting, 2023)
This study aims to analyze the influence of organizational culture, quality of human resources, motivation, and work discipline on the performance of the employees of Radio Republik Indonesia, Riau Islands Province partially and simultaneously. This research uses quantitative methods and uses a questionnaire with a Likert scale. Total population amounted to 123 respondents while the sampling technique using saturated samples amounted to 120 respondents. Data testing was analyzed using multiple linear regression and hypothesis testing using partial t test and simultaneous F test. The results of the t test show (1) organizational culture has a significant effect on the performance of the employees of Radio Republik Indonesia in the Riau Islands Region, (2) The quality of human resources has a significant effect on the performance of the employees of Radio Republik Indonesia in the Riau Islands Province, (3) Motivation has a significant effect on employee performance. Radio Republik Indonesia, Riau Islands Province, (4) Work Discipline has a significant effect on the performance of the employees of Radio Republik Indonesia, Riau Islands Province. Simultaneous F test results show that organizational culture, quality of human resources, motivation, and work discipline simultaneously influence the performance of the employees of Radio Republik Indonesia, Riau Islands Province.